Male sive celice in velika siva polja - Hafner, Miha (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2014)
The increasing use of neuroscience-based evidence in criminal courts raises many questions in evidentiary criminal law. The first grey area is connected to the limited probative value of such material that is intertwined with the numerous limitations of modern methods of neuroimaging and their speculative nature. The use of structural brain images in criminal procedure can be considered admissible in Slovenian law, despite the deep intrusion into one%s privacy. The accused and the witness can be subjected to the neuroimaging procedure even against their will. However, the opposite can be said about approaches that use neuroscience as an interrogation tool. Due to the privilege against self-incrimination and the ban of the use of medical interventions and agents, such methods are deemed inadmissible in criminal procedure, since they gain testimonial evidence by circumventing the interrogated person´s will to testify.
Keywords: možgani; neurology; nevrologija; criminal law; kazensko pravo; kazniva dejanja; dokazi